AtLSG1-2 Regulates Leaf Growth by Affecting Cell Proliferation and the Onset of Endoreduplication and Synergistically Interacts with AtNMD3 during Cell Proliferation Process - Zhao, Huayan; Lü, Shiyou; Xiong, Liming (Frontiers in Plant Science, 2017)
AtLSG1-2 is a circularly permuted GTPase required for ribosome biogenesis and recently shown to be involved in early leaf development, although it was unclear how AtLSG1-2 affects leaf growth. Here, we found that atlsg1-2 mutants had reduced leaf size as a result of decreased cell size and cell number. Leaf kinematic analysis and CYCB1;1::GUS expression pattern in atlsg1-2 mutant indicated that loss of function of AtLSG1-2 delays the transition from cell division to cell expansion. Decreases in ploidy levels and trichome branch number suggest that AtLSG1-2 deficiency suppresses endoreduplication. Real-time PCR analysis showed that genes specifically expressed in the proliferation stage were highly expressed and those involved in endoreduplication were differentially regulated. LSG1 is known to mediate the recruitment of nucleocytoplasmic shuttling protein NMD3 back to the nucleus in yeast, yet their relationship was unclear in plants. Our genetic analysis revealed that the atlsg1 atnmd3 double mutant displayed enhanced phenotypes as compared with the respective single mutant and that AtLSG1-2 and AtNMD3 synergistically affect the cell proliferation process.